Participation in the Pentecostal Liturgy : An Ecclesiology of the Prophethood of All Believers - Davis, Ryan, (Global Pentecostal and Charismatic Studies ;, 2026)
How can the prophethood of all believers reshape Pentecostal worship? In Participation in the Pentecostal Liturgy, T. Ryan Davis, PhD, offers a bold vision where every believer is empowered to participate fully in the church's liturgy. Rooted in the outpouring of the Spirit at Pentecost, Davis develops a pneumatological ecclesiology that challenges traditional views of participation and redefines the altar as a space of shared transformation. Through the concept of an altar hermeneutic, this book invites Pentecostal communities to recover their egalitarian impulse and make room for all to actively take part in the church's community gatherings of worship.